Epidemiological profile of women with breast cancer in a public hospital in the Federal District of Brazil - Jorge, Jardeson Saraiva; Siqueira, Fabio; Leal, Jessica Vick de Oliveira (Mastology, 2021)
Introduction: In Brazil, for the 2020–2022 triennium, the estimated incidence of breast cancer in women was 66,280/year. It is the most incident type of cancer in all Brazilian regions. Several risk factors are associated with the probable etiology of breast cancer, though the complexity of the disease makes it difficult to define its main cause. Objective: To investigate the prevalence of factors associated with breast cancer in an outpatient population at a public hospital in the Federal District, and to verify the epidemiological profile of this population to compare the data obtained with data published in the literature. Method: This is a descriptive cross- sectional study, with 115 participants diagnosed with breast cancer undergoing treatment in a highly complex unit of oncology care in the Federal District between July and October 2020. Data collection was done through a questionnaire. The electronic medical record was consulted to complement the data. Results: The majority of women were brown, married, with an average age of 52. Hormone therapy was reported by 73.9%, early menarche by only 33.9% and late menopause by 25.2%. Most had children before the age of 30 and more than 80% breastfed. A family history of breast cancer was present in 30.4% of the sample. The consumption of alcoholic beverages was reported by more than half of the women, but the use of cigarettes was denied by the majority. The practice of some physical activity before the diagnosis of cancer was reported by 69.6%. Most were overweight or had some degree of obesity. Non- special invasive carcinoma was the most common type. Conclusions: This study showed that the main factors present in the sample were: advanced age, alcohol consumption, use of hormone therapy and overweight.